2015
DOI: 10.1038/srep15670
|View full text |Cite
|
Sign up to set email alerts
|

Associations of prodynorphin sequence variation with alcohol dependence and related traits are phenotype-specific and sex-dependent

Abstract: We previously demonstrated that prodynorphin (PDYN) haplotypes and single nucleotide polymorphism (SNP) rs2281285 are associated with alcohol dependence and the propensity to drink in negative emotional states, and recent studies suggest that PDYN gene effects on substance dependence risk may be sex-related. We examined sex-dependent associations of PDYN variation with alcohol dependence and related phenotypes, including negative craving, time until relapse after treatment and the length of sobriety episodes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In the current analysis, although it was not statistically significant (P=0.154), the PDYN rs2281285 AG+GG genotypes (20.19±6.62) had a higher SCS total score than AA genotypes (16.31±8.98), suggesting the association of opiate negative craving with the PDYN rs2281285 variant. This is consistent with previous investigations on alcohol-dependent subjects, which demonstrated an association between the rs2281285 minor G allele and increased negative craving [27][28][29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current analysis, although it was not statistically significant (P=0.154), the PDYN rs2281285 AG+GG genotypes (20.19±6.62) had a higher SCS total score than AA genotypes (16.31±8.98), suggesting the association of opiate negative craving with the PDYN rs2281285 variant. This is consistent with previous investigations on alcohol-dependent subjects, which demonstrated an association between the rs2281285 minor G allele and increased negative craving [27][28][29].…”
Section: Discussionsupporting
confidence: 93%
“…The present study was undertaken with the aim of exploring whether PDYN gene polymorphisms (rs2281285, rs2225749 and rs910080) have an effect on the intensity of depressive symptoms and negative craving in heroin addicts due to the contribution of dynorphin to negative emotional states and to drug-seeking behavior as a result of negative reinforcement. In the literature, the contribution of the PDYN gene to the induction of negative craving [27][28][29] and depression [27] was investigated in only alcohol-dependent subjects. A few studies have examined the effects of PDYN genotypes on susceptibility to opiate addiction in different populations [17][18][19][20][21][22]30].…”
Section: Discussionmentioning
confidence: 99%
“…toxicity and/or resetting of allostatic threshold) as well as vulnerability to comorbid mood and anxiety disorders and, especially, SID in male but not female alcoholics. Interestingly, recent analyses of genetic effects on alcoholism‐related phenotypes also indicate the presence of sex‐dependent effects that are also phenotype‐specific: for example, the same genetic variant being associated with alcoholism in males, and with increased propensity to drink in negative emotional situations, negative craving and shorter time for post‐treatment relapse in female but not male alcoholics . Further research is needed to determine which genetic, toxic or other underlying biological and psychosocial mechanisms are responsible for associations between propensity to drink in negative emotional situations and life‐time history of comorbid MDD, SID or AnxD in male and female alcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice lacking Pdyn showed significantly lower preference and consumption of ethanol, but interestingly, no differences in LORR (Blednov et al 2006). In humans, multiple studies have demonstrated that PDYN haplotypes and individual SNPs (rs2281285) are associated with alcohol dependence and propensity to drink in negative emotional states (Flory et al 2011; Karpyak et al 2013; Winham et al 2015), and that decreased methylation levels of PDYN are associated with craving and alcohol consumption (D’Addario et al 2017).…”
Section: Discussionmentioning
confidence: 99%